Pliocene river capture and incision of the northern Altiplano: Machu Picchu, Peru - Gérard, Benjamin (2020)
The Abancay Deflection, forming the northern edge of the Altiplano in the Peruvian Andes, is a remarkable geomorphological feature marking the along-strike segmentation of the Andes. Little is known about the timing and spatial distribution of exhumation in this area. To constrain the exhumation history of the Abancay Deflection and its drivers, we present apatite (U–Th)/He and fission-track thermochronology data from samples collected along an elevation transect at Machu Picchu. Geomorphological analysis demonstrates recent and continuing drainage reorganization recorded by the spatial distribution of the normalized steepness index (ksn) and normalized integrated drainage area (χ) parameters. Thermochronologically derived cooling rates are converted into exhumation using regionally constrained geothermal gradients between 16 and 26°C km−1. Time–temperature inversions imply steady and slow exhumation (<0.05 km Ma−1) between 20 and 4 Ma, followed by rapid exhumation (>0.9 km Ma−1) since 4 Ma. The timing of rapid exhumation, combined with the geomorphological analysis, suggests that fluvial capture of the previously endorheic Altiplano by the Urubamba River drove recent incision and exhumation. Depending on the value of the geothermal gradient used, total exhumation since 4 Ma can be explained by river incision alone or requires additional exhumation driven by tectonics, possibly associated with movement on the Apurimac fault.